Now I'm 3: Young Children's Concepts of Age, Aging, and Birthdays. (March 2019) - Woolley, Jacqueline D.; Rhoads, Amanda M.
In two studies, we examined 99 3- to 5-year-old American children's concepts of age, aging, and birthdays. Previous research has shown that preschool-age children understand that all living beings grow, and that growth is a biological process. Humans, however, are distinct from other living things in that we attach great significance to the aging process. Specifically, in Western cultures, we have an annual ritual to celebrate the day we were born—the birthday party. Thus, although the biological mechanism of aging is continuous and invisible, it is marked by discrete yearly celebrations. We examine the proposal that, in part due to its salience as a cultural ritual, children interpret the birthday party as playing a causal role in the aging process. Results indicate that young children understand certain important biological aspects of the aging process but exhibit confusion regarding others, including the causal role of the annual birthday party.